Pesquisa do vírus da raiva em quirópteros no Estado de Roraima pelo método de RT-PCR - Souza, James Rodrigues de (2011)
Rabies is an infectious disease that affects mammals, including human beings. Present on all continents except Antarctica. It is caused by a Lyssavirus. Dogs are considered responsible for the maintenance and transmission of rabies to humans. But in recent years the bats have become a potential source of transmitting rabies to animals and human beings in the Americas. In 2010, Brazil recorded three cases of human rabies. One of them was caused by an attack of bat. Recently, several outbreaks of human rabies transmitted by vampire bats were reported in the Amazon region, so far, in the state of Roraima there is no record of cases of human rabies. This study is aimed to detect the presence and circulation of rabies virus in bats in the state of Roraima, as well as to identify the species involved, it includes, also, the necessity of strengthen the network of epidemiological and environmental surveillance of rabies. The technique followed by reverse transcriptase polymerase chain reaction (RT-PCR) was used for virus research involving brain tissue of bats that were collected by teams of environmental and epidemiological surveillance, belonging to the Department of Health and the health protection agency of Roraima. Species of Bats were identified using dichotomous keys available for bats in Brazil and other Latin American countries. In total of 94 bat samples were analysed. The samples tested were negative for rabies. It can not be said, however, that the rabies virus does not circulate in Roraima. This research identified 19 species of bats distributed in six family. On the other hand, the research points to a richness and abundance of species of bats. This study identified one family (Vespertilionidae) and five species of bats (Diaemus youngi, Noctilio albiventris, Myotis nigricans, Eptesicus diminutus e Cynomops planirostris) not yet reported to the State. Vampire bats were identified in five municipalities. Considering the epidemiological and environmental importance of bats for ecosystems, this study is contributing to the increase of knowledge about both environmental surveillance of rabies and diversity of bats.